Stability Control Strategy of HXD1 Eight-axle Electric Locomotive - ZHANG Tao; XIAO Jiabo (机车电传动)
By analyzing the stability control of HXD1 eight-axle electric locomotive, a stationary control strategy based on quasi constant speed control mode and multi-model self-adaption construction was proposed. The realization methed and control effect of control strategy was demonstrated,the feasibility of the control strategy was verified by simulation test and field test. The experimental results showed that the control strategy could be adaptive control according to the locomotive operation condition, and ensure locomotive running smoothly.